Combined aromatase, CDK4/6 and PI3K blockade using letrozole/abemaciclib/LY3023414 in endometrial cancer - Panagiotis A. Konstantinopoulos; Niya Xiong; Carolyn Krasner; Joyce F. Liu; Hannah Sawyer; Madeline Polak; Hope Needham; Megan Geddes; Lani Koppermann; Meghan Shea; Cesar Castro; Su-Chun Cheng; et al. (Elsevier, 2024)
Several lines of preclinical evidence indicate that combining PI3K and CDK4/6 inhibitors may further enhance the efficacy of hormonal therapy by overcoming de novo and acquired resistance to PI3K and CDK4/6 blockade. We evaluated the combination of abemaciclib, letrozole and LY3023414 (an orally available, selective inhibitor of the class I PI3K isoforms and mTORC1/2) in recurrent endometrial cancer (EC). This study was terminated prematurely after 5 patients initiated protocol therapy due to discontinuation of further development of LY3023414. We report our findings from these patients, including one with recurrent endometrioid EC with AKT1, CTNNB1 and ESR1 hotspot mutations who had previously progressed through letrozole/everolimus and achieved a partial response to letrozole/abemaciclib/LY3023414.